Inisiasi Protocorm Like Bodies (PLB) Dendrobium sylvanum - Siti Malahayati; Noval Noval; Setia Budi (Jurnal Pelayanan Kefarmasian dan Sains, 2022)
Genus of Dendrobium orchid produces secondary metabolites namely medicinal alkaloid, the main alkaloid in dendrobium is dendrobine. Orchid plant parts that contain secondary metabolites in large quantities are in the form of protocorm like bodies (PLB). This research is about how to do an initiation of PLB from the seed of Dendrobium sylvanum. The aim of this research is to determine the concentration of giberelin (GA3) in Murashige and Skoog (MS) medium for PLB optimal initiation. Seed culture was cultivated in MS medium supplemented with GA3 in 3 concentrations: GA3 1 ppm; GA3 2 ppm; and GA3 4 ppm. The result showed the concentration that can give the optimal growth is GA3 1 ppm based on the appeareance of PLB, colour of PLB, diameter of PLB, growth index, and anatomy of PLB.